Polskie Stronnictwo Ludowe w regionie krakowskim w latach 1945-1946 - FIOŁEK, Damian (Historia i Świat, 2018)
The article presents the research of students at the Siedlce University. The author of the text "Polish People’s Party in the Krakow region in 1945-1946" is a student at the Institute of History and International Relations.